Feasibility of oral HIV self-testing in female sex workers in Gaborone, Botswana - Shava, Emily; Bogart, Laura M.; Manyake, Kutlo; Mdluli, Charlotte; Maribe, Kamogelo; Monnapula, Neo; Nkomo, Bornapate; Mosepele, Mosepele; Moyo, Sikhulile; Mmalane, Mompati; Bärnighausen, Till; Makhema, Joseph; et al. (PLOS ONE, 2021)
Background Oral HIV self-testing (HIVST) may be useful for increasing testing in persons at elevated risk of acquiring HIV. Methods We conducted a pilot study to evaluate the feasibility (defined by uptake) of HIVST among FSW in Gaborone, Botswana. FSW age 18 years and above were recruited through a non-governmental organization serving FSW. FSW with unknown or negative HIV status at screening performed HIVST in the study clinic following brief training. FSW testing HIV-negative were each given two test kits to take home: one kit to perform unassisted HIVST and another to share with others. Feasibility (use) of HIVST (and sharing of test kits with others) was assessed in these women at a study visit four months later. Results Two hundred FSW were screened. Their average age was 34 years (range 18-59), and 115 (58%) were HIV-positive. Eighty-five (42%) tested HIV-negative at entry and were eligible to take part in the HIVST pilot study. All 85 (100%) agreed to take home HIVST kits. Sixty-nine (81%) of these 85 participants had a follow-up visit, 56 (81%) of whom reported performing HIVST at a mean of three and half months after the initial visit. All 56 participants who performed HIVST reported negative HIVST results. Fifty (73%) of the 69 participants who took HIVST kits home shared them with others. Of the 50 women sharing HIVST kits, 25 (50%) shared with their non-client partners, 15 with a family member, 8 with friends, and 3 with a client. One participant did not test herself but shared both her test kits. Most participants 53/56 (95%) found oral HIVST very easy to use whilst 3/56 (5%) felt it was fairly easy. Conclusion Oral HIVST is feasible among FSW in Gaborone, Botswana. The majority of FSW used the HIVST kits themselves and also shared extra HIVST kits with other individuals.